Early British socialism and the "religion of the new moral world" - Lucas, E (2021)
This thesis will be concerned with the question of the relationship between Owenite socialists and religion. In this thesis I will seek to untangle and disambiguate existing scholarly accounts of the relationship between Owenite socialism and religion. I will then identify how Owenites offer a re-conception of the nature of ‘religion’ as advanced through knowledge of the natural and social world, as a prospective source of solidarity which could serve as the unifying bond for communities, and as constituted by ethical conduct. I will demonstrate how these Owenites’ critique of contemporary religion was shaped by the particular conditions of the early nineteenth century, conditions which represented a problem to which they offered a solution. I then show how this solution was formed by drawing upon the traditions of natural theology, popular religion, deism, and Rational Dissent. I show how this solution was formed through a sincere and considered reflection upon the problem of religious truth. I will then show the importance of this reimagination of religion to their understanding of socialism. I demonstrate that these Owenites understood their socialism to be, in part, a project of religious reform, as rivalling the Oxford Movement and as a successor to the Reformation. Their religious interests were not an eccentric adornment to their socialism, an outdated residue yet to be shed and encumbering the development of a mature socialism, or merely instrumental to their temporal goals. Instead, their ambitions of religious reform were grounded in the philosophical preoccupations which animated their socialism. They conceived theological falsehoods as an obstacle to the triumph of socialism. And they argued that one should become a socialist, in part, precisely because it created the conditions for the popularisation of religious virtue. I conclude by identifying some implications of the argument of this thesis.